2018
DOI: 10.1111/gfs.12386
|View full text |Cite
|
Sign up to set email alerts
|

Reducing nitrogen leaching losses in grazed dairy systems using an Italian ryegrass‐plantain‐white clover forage mix

Abstract: In grazed agricultural systems, animal urine patches are the major source of nitrogen (N) leaching losses and can cause a decline in water quality. Urine‐N rates often exceed plant requirements, and there is a need for mitigation options to reduce the impact of agriculture on the environment. One approach is to use alternative forages to reduce urine‐N loading rates, or to increase N uptake. This study used lysimeters to determine the N leaching losses, dry matter yields and N uptake following ruminant urine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…However, the model version used also takes into account the effects of plantain on urinary N excretion by animals and the subsequent nitrogen load. Such an effect is estimated based on studies undertaken as part of the Forages For Reduced Nitrate Leaching Programme, which assessed the impact of various forages including plantain on nitrate leaching [ 10 , 14 , 18 , 19 , 30 , 31 ]. The full description and sensitivity analysis for implementation of plantain in Overseer ® was described by [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the model version used also takes into account the effects of plantain on urinary N excretion by animals and the subsequent nitrogen load. Such an effect is estimated based on studies undertaken as part of the Forages For Reduced Nitrate Leaching Programme, which assessed the impact of various forages including plantain on nitrate leaching [ 10 , 14 , 18 , 19 , 30 , 31 ]. The full description and sensitivity analysis for implementation of plantain in Overseer ® was described by [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…with greater growth at low temperatures) [ 13 , 14 ]. However, the benefits of these strategies in mitigating the environmental footprint of dairy systems were investigated in a short time frame and/or over a small physical scale, such as in lysimeter studies [ 18 ]. Whether the suggested mitigation strategies function over larger physical and temporal scales, or whether there are secondary effects on farm productivity and profitability, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst a major emphasis of early papers was on the improvement and productivity of grasslands, there has been an increased emphasis on the ecosystem services that grasslands provide across the globe (D’Ottavio et al, 2018) and the ecological and societal pressures on grassland agriculture. Therefore, we have seen papers submitted that seek to understand nitrogen responses in terms of efficiency of plant responses (Sandaña et al, 2019) and the farming system implications of the role of nitrogen on forage quality and productivity, animal production and nitrogen leaching (O’Connor et al, 2019) including a revisitation of the role of legumes in this context (Guy et al, 2018; Niderkorn et al, 2019; Woods et al, 2018).…”
Section: The Most Recent Years (2018–2019)mentioning
confidence: 99%
“…Carlton et al (2018) found in a lysimeter study using Templeton sandy loam soil, 82% and 74% reductions in mineral N leaching from perennial ryegrass/white clover with plantain (PRG/WC/P), compared with traditional PRG/WC, when urine (700 kg N −1 ha −1 ) was applied in December and February, respectively. Woods et al (2018) found a pasture mix of Italian ryegrass, white clover and plantain (IRG/WC/P) leached 46% less mineral N than PRG/WC, when urine (700 kg N −1 ha −1 ) was applied in March, to a Templeton sandy loam soil. Welten et al (2019) found 15%, 27% and 52% reductions in mineral N leaching from pure plantain swards compared with pure PRG swards, for summer, autumn and winter applied urine (622 kg N −1 ha −1 ), respectively; this study was conducted on a Horotiu silt loam soil.…”
Section: Introductionmentioning
confidence: 99%